Market access provisions in regional trade agreement - Antoni Estevadeordal; Matthew Shearer; Kati Suominen (Inter-American Development Bank (IDB), 2009)
Regional trade agreements (RTAs) have proliferated over the past decade around the world to cover nearly half of global trade. The number of RTAs notified to the WTO is approaching 200, while the total number of RTAs around the world exceeds 300. The global RTA spree has forged a veritable spaghetti bowl of multiple and often overlapping agreements.
hdl:11319/2524
Keywords: 330